Low-density lipoprotein cholesterol goal attainment and mortality in ischaemic heart disease: a two-year observational study - Ying Hui Mak; Fionn Chua; Xuan Han Koh; Vern Hsen Tan; Zhong Hui Lee; Audrey Lam; Kim Leng Tong; Colin Yeo; Weien Chow; Wann Jia Loh (Singapore Medical Journal)
Introduction: Achieving low-density lipoprotein cholesterol (LDL-C) levels is key to preventing atherosclerotic cardiovascular events. However, many high-risk cardiovascular patients still experience poor LDL-C goal attainment and receive suboptimal lipid-lowering therapy (LLT) prescriptions. Herein, we evaluated LLT prescription patterns, LDL-C goal attainment and cardiovascular mortality among this population group in Singapore. Methods: This prospective observational cohort study included 555 patients with ischaemic heart disease (IHD) admitted to the hospital in 2020. The LLT prescriptions, corresponding LDL-C levels and cardiovascular outcomes were assessed over a 24-month period. Results: Most participants were male (82.3%), with 48.5% identified as Chinese. High-intensity statin prescriptions increased from 45.4% at hospital admission to 87.1% at discharge and remained stable at approximately 80% at 6, 12, and 24 months post-discharge. Combination LLT prescriptions increased from 12.3% at discharge to 33.8% by 24 months. Ezetimibe was the most commonly prescribed second-line LLT (40.8%), followed by inclisiran (1.09%) and anti-proprotein convertase subtilisin/kexin type 9 monoclonal antibody therapies (0.87%). Over 24 months, LDL-C goal attainment rates were 22.1% for LDL-C < 1.4 mmol/L and 47.2% for LDL-C < 1.8 mmol/L. Multivariable Cox proportional hazards regression indicated that achieving LDL-C < 1.8 mmol/L goal was associated with a reduction in all-cause mortality at 24 months (hazard ratio 0.53, 95% confidence interval 0.30–0.94, P = 0.030). Conclusion: Treatment gaps in lipid management persist in 80% of the study population, indicating that statin monotherapy alone is insufficient to achieve LDL-C goals. Greater efforts to improve LDL-C goal attainment rates in high-risk cardiovascular patients are imperative.